2021
DOI: 10.55374/jseamed.v5i2.90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors in the Decline of Renal Function Among Outpatients Attending a Community Hospital, Central Thailand

Abstract: Introduction: Chronic kidney disease (CKD) is recognized as global public health issue especially affecting developing countries including Thailand. The epidemiologic data in the decline of renal function and the risk factors among Thai patients especially in community hospital settings were limited. Methods: A cross-sectional study was conducted to identify the prevalence and associated risk factors in the decline of renal function among outpatients in Thaluang Community Hospital, Lop Buri Province, cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The results of this study agreed with that of Chamnanmont et al (26) investigating the prevalence and associated factors for the decline of eGFR among patients attending a community hospital and reported the incidence of eGFR<60 mL/min/1.73m 2 was 20.3%; risk factors included age, NSAIDs use and presenting high blood pressure.…”
Section: /11 Journal Of Southeast Asian Medical Research E0153supporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study agreed with that of Chamnanmont et al (26) investigating the prevalence and associated factors for the decline of eGFR among patients attending a community hospital and reported the incidence of eGFR<60 mL/min/1.73m 2 was 20.3%; risk factors included age, NSAIDs use and presenting high blood pressure.…”
Section: /11 Journal Of Southeast Asian Medical Research E0153supporting
confidence: 91%
“…On the other hand, among patients with atrial fibrillation, studies compared the effects of nonvitamin K antagonist oral anticoagulant (NOAC) and warfarin; NOAC provided more reno-protective effects than warfarin. (24)(25)(26) Therefore, further investigation regarding drug use is crucial for establishing a solid conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Thailand, the National Health Examination Survey VI in 2019 demonstrated that 25% of Thai adults aged ≥ 15 years suffer from hypertension (HT) [2]. Raised BP is a leading cause of end-organ damage, including ischemic heart disease, stroke, and chronic kidney disease [3][4][5][6][7]. Furthermore, a few studies reported the relationship between HT and liver dysfunction [8,9].…”
Section: Introductionmentioning
confidence: 99%